Pengaruh Audit Tenure, Leverage, Financial Distress dan Audit Report Lag Terhadap Opini Audit Going Concern - Kamilah Husna; Ratih Qadarti Anjilni (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research was conducted to analyze the effect of Audit Tenure, Leverage, Financial Distress and Audit Report Lag on Audit Opinion Going Concern. The research was conducted on Energy Sector Companies listed on the Indonesia Stock Exchange in 2019-2023. This type of research is associative quantitative research. The methodology used is Logistic Regression because the dependent variables of this study are in the form of dummy variables. Sample selection was carried out using the Purposive Sampling method from secondary data in the form of Financial Statements and found as many as 12 sample companies with a total of 5 years of observations, so that the total sample in this study was 60 observation data. Hypothesis testing was carried out using the Eviews series 12 application. The results of the study show that Audit Tenure, Leverage, Financial Distress and Audit Report Lag have an effect on Audit Opinion Going Concern. Audit Tenure has no effect on Audit Opinion Going Concern, Leverage has no effect on Audit Opinion Going Concern, Financial Distress has effect on Audit Opinion Going Concern, and Audit Report Lag has no effect on Audit Opinion Going Concern.